Pemertahanan Leksikon Fauna Air Tawar di Kalangan Remaja - Hidayatullah, Fathi Ridwan; Rosidin, Odien; Damanhuri, Yudi (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2023)
In Sundanese, there is a lexicon of freshwater fauna. This article will describe how the freshwater fauna lexicon of Sundanese society is maintained among teenagers in Leuwiliang sub-district. Lexicon of aquatic fauna which still survive and which have become extinct or displaced. This is sociolinguistic research with an ecological approach. The research uses descriptive analysis methods with qualitative and quantitative data sources. The results of the research show that the lexicon of freshwater fauna among teenagers has begun to shift. The research data amounts to 84 freshwater fauna lexicons. From the results of interviews and questionnaires, information was obtained that 19 (22.6%) freshwater fauna lexicons were no longer used in daily activities, while 65 (77.4%) freshwater fauna lexicons were still used. It is hoped that the results of the research will become a cultural record in the treasures of the Sundanese language so that it can reduce the extinction of the freshwater fauna lexicon of the Sundanese people.Kesywords: lexicon; maintenance; sociolinguisticsAbstrakDalam bahasa Sunda terdapat leksikon fauna air tawar. Artikel ini akan mendeskripsikan bagaimana pemertahanan leksikon fauna air tawar masyarakat Sunda pada kalangan remaja di kecamatan Leuwiliang. Leksikon fauna air apa yang masih bertahan dan yang sudah punah atau tergeser. Ini adalah penelitian sosiolinguistik dengan ancangan ekologi. Penelitian menggunakan metode analisis deskriptif dengan sumber data kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa leksikon fauna air tawar pada kalangan remaja sudah mulai bergeser. Data penelitian berjumlah 84 leksikon fauna air tawar. Dari hasil wawancara dan penyebaran kuisioner diperoleh informasi  bahwa 19 (22,6%)  leksikon fauna air tawar sudah tidak lagi digunakan dalam kegiatan sehari-hari sedangkan 65 (77,4%) leksikon fauna air tawar masih digunakan. Hasil penelitian diharapkan menjadi sebuah catatan budaya dalam khazanah kebahasan Sunda sehingga dapat mengurangi  kepunahan leksikon fauna air tawar masyarakat Sunda. Kata kunci: leksikon; pemertahanan; sosiolinguistik